PRODUKSI BIOETANOL DARI LIMBAH BATANG KELAPA SAWIT (Elaeis guineensis) MENGGUNAKAN Zymomonas mobilis DENGAN PERLAKUAN CRUDE ENZIM Trichoderma reesei DAN Aspergillus niger - Sindhea Nurmala Santi; Trianik Widyaningrum (Universitas Islam Negeri Sumatera Utara, 2022)
Bioethanol is an alternative energy that is starting to be needed, along with the depletion of petroleum reserves. Bioethanol can be obtained from various wastes, including palm oil trunk waste which contains 86.03% cellulose. The purpose of this study was to determine the production of bioethanol from oil palm trunk waste by treatment with crude enzymes Trichoderma reesei and Aspergillus niger. This research is an experimental study using a completely randomized design, namely the ratio of crude enzymes from Trichoderma reesei and Aspergillus niger (0:0), (1:0), (0:1), (1:1), (2:1), (1:2), (3:1), (1:3) on sugar and bioethanol content of fermented oil palm stem waste using Zymomonas mobilis. Sugar content was measured using the DNS method, bioethanol content was measured using an alcoholmeter. Data were analyzed using one way ANOVA. The results showed that the crude enzymes T. reesei and A. niger could increase the sugar content, namely the ratio of crude enzymes T. reesei and A. niger 3:1 (11.89 g/mL). The highest bioethanol content was in the ratio of crude enzymes T. reesei and A. niger (2:1), which was 2.34%.